(untitled) (Indian Journal of Arid Horticulture, 2025)
The experiment was conducted to study the effect of drip irrigation and mulches on water use efficiency and productivity of aonla cv. Narendra Aonla-10 (NA-10). There were four irrigation regimes in terms of IW/CPE ratios of 1.0, 0.8, 0.6 and 0.4 and three types of mulches, namely black polythene, paddy straw and control (no mulch). The results indicated that aonla plants drip irrigated at 0.6 IW/CPE had higher leaf nitrogen status as compared to higher and lower levels of irrigation. Leaf nitrogen, potassium, calcium and magnesium were higher in paddy straw mulched trees, while phosphorus content was higher under polythene mulching. Fruits attained significantly higher fruit length, diameter, weight and volume at 1.0 IW/ CPE. The higher levels of irrigation, viz., 0.8 and 1.0 1W/CPE improved fruit size but drip irrigation at 0.6 IW/CPE coupled with black polythene mulching resulted in optimum fruit yield and quality parameters such as total sugar content, ascorbic acid and acidity contents of aonla cv. NA-10. Thus, it helps in cutting down the water requirement of aonla to 0.6 IW/CPE (60% evaporation replenishment) with drip irrigation and black polythene mulching for optimum fruit yield and quality.